Is there such a Thing called Scientific Waste? - Hendrik P. van Dalen; Arjo Klamer (Tinbergen Institute, 2005)
Science is a winner-take-all profession in which only few contributions get excessive attention and the large majority of papers_new remains receives scant or no attention. This so-called `waste' together with all the competitive strategies of scientists seeking attention is part and parcel of any creative profession and not a worrisome fact as the price society pays for human ingenuity is extremely small: 0.0006 percent of world income goes into the publication of scientific research. The more worrisome features of competition in academic economics reveal themselves not through ordinary citation or publication statistics or competitive attention seeking strategies. The badly designed use of market principles in which citations and publications have become the sole measuring rod of scientific `productivity' deserve more attention instead of the excessive focus of attention on uncitedness as such.
Keywords: A14; H4; O34; 330; economic science; public good; citations; wasteful competition; Wissenschaftsforschung; Wissenschaft; Kosten-Wirksamkeits-Analyse